THE METAFUNCTIONS REVEALED: EFL LEARNERSâ€™ EXPERIENCE IN MAKING SENSE OF THE TEXT - Bumela, Lala (Universitas Pendidikan Indonesia, 2012)
Abstract: This study was primarily intended to capture the English as foreign language learnersâ€™ (henceforth EFL learners) experience in making sense of the text: to what extent the meaning-making elements of the texts are comprehended and interpreted by EFL learners as readers.Â The investigation itself was centered around the notion of metafunctions â€“ ideational, interpersonal, and textual â€“ of the text for several reasons.Â This study tries to reveal how EFL learners make sense of the two selected articles taken from â€œThe Jakarta Postâ€ entitled â€œAustralia Stops Some Cattle Exports to Indonesiaâ€ and â€œAustraliaâ€™s ban on Cattle Exports to RI Politicalâ€.Â The two articles were downloaded from thejakartapost.com in June 2011.Â The main reason why newspaper articles were chosen was because, as Lehtonen (20006) puts it, â€œnewspaper descriptions of reality are always produced from a certain perspectiveâ€.Â In the context of this study, the two groups of respondents were involved: two respondents who have not taken Functional Grammar class (group one) and two respondents who have attended functional grammar class (group two).Â The four respondents are English Department students at one private university in Kuningan, West Java.Â The study shows Â that reading is not simply a matter of recognizing the alphabetical orders of the texts.Â Reading is, in fact, a discursive activity which is influenced by the previous textual experiences.Â The quality of interpretation is always affected by the background knowledge of readers, the ability in recognizing the features of the texts, and, of course, the ability to identify the metafunctions of the texts.Â An interaction with a discourse will automatically generate a new discourse.Â The reading of particular texts will in turn trigger the reading (and the discussion and analysis) of the other texts. Â Key words: metafunctions, meaning making, metacognitive system, subculture